Plerixafor improves the endothelial health balance. The effect of diabetes analysed by polychromatic flow cytometry. (August 2016) - Cappellari, Roberta; D'Anna, Marianna; Avogaro, Angelo; Fadini, Gian Paolo
Abstract: Background and aims: Diabetes damages the endothelium and reduces the availability of bone marrow (BM)-derived endothelial progenitor cells (EPCs). The mobilization of hematopoietic stem cells (HSCs) and EPCs in response to G-CSF is impaired by diabetes, owing to CXCL12 dysregulation. We have previously shown that the CXCR4/CXCL12 disruptor plerixafor rescues HSC and EPC mobilization in diabetes. We herein explored the effects of plerixafor on HSCs, EPCs, and circulating endothelial cells (CECs) in patients with and without diabetes. Methods: We re-analysed data gathered in the NCT02056210 trial, wherein patients with (n = 10) and without diabetes (n = 10) received plerixafor to test stem/progenitor cell mobilization. We applied a novel and very specific polychromatic flow cytometry (PFC) approach to identify and quantify HSCs, EPCs, and CECs. Results: We found that 7-AAD - Syto16 + CD34 + CD45 dim HSC levels determined by PFC strongly correlated to the traditional enumeration of CD34 + cells, whereas 7-AAD - Syto16 + CD34 + CD45 neg KDR + EPCs were unrelated to the traditional enumeration of CD34 + KDR + cells. Using PFC, we confirmed that plerixafor induces rapid mobilization of HSCs and EPCs in both groups, with a marginally significant defect in patients with diabetes. Plerixafor reduced live (7-AAD - ) and dead (7-AAD + ) Syto16 + CD34 bright CD45 neg CD146 + CECs more in patients without than in those with diabetes. The EPC/CEC ratio, a measure of the vascular health balance, was increased by plerixafor, but less prominently in patients with that in those without diabetes. Conclusions: In addition to rescuing defective mobilization associated with diabetes, plerixafor improves the balance between EPCs and CECs, but the latter effect is blunted in patients with diabetes. Highlights: We explored the effects of plerixafor on circulating mature end progenitor endothelial cells. We applied a novel polychromatic flow cytometry panel. Plerixafor rescued stem and progenitor cell mobilization in diabetes. Plerixafor significantly reduced circulating mature endothelial cells. Plerixafor improved the vascular health balance, but less prominently in diabetic vs non diabetic patients.